Blurring Boundaries: Negotiating Researchers’ Positionality and Identities in Digital Qualitative Research - Lavorgna, Anita; Sugiura, Lisa (Italian Sociological Review, 2022)
This contribution discusses a series of methodological, ethical, and ontological challenges encountered by the authors during a series of recent socio-criminological studies based on digital ethnography and investigating sensitive and emotive issues. Particularly, we will discuss the practical difficulties we encountered in navigating several increasingly blurred boundaries, such as those among: (1) the researchers’ private and public academic/personal selves online; (2) the shifting of the traditional power imbalances between the researcher and research participants; (3) concerns over impartiality in research; and (4) elements of ethnography and autoethnography becoming obfuscated. We consider these dilemmas in the context of the pervasiveness of digital technologies within contemporary social life, such that we as researchers are always simultaneously on and offline, with our studies at risk of becoming all-consuming and encroaching on all areas of our lives. We will see how these blurred boundaries entail an inescapable continuous negotiation of researcher identity and positionality, and some of their practical consequences. We aim to encourage further discussion about these novel challenges faced whilst undertaking online research, and re-examination of the related ethical principles regarding these contexts.